Bird population and bird hunting in the rural ecosystem of Cijambu, Sumedang, West Java, Indonesia - SUROSO SUROSO; JOHAN ISKANDAR; SUSANTI WITHANINGSIH; DEDEN NURJAMAN; BUDIAWATI S. ISKANDAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suroso, Iskandar J, Withaningsih S, Nurjaman D, Iskandar BS. 2023. Bird population and bird hunting in the rural ecosystem of Cijambu, Sumedang, West Java, Indonesia. Biodiversitas 24: 4470-4484. Some rural West Java ecosystems have a high bird species diversity because they have forests, bamboo talun, mixed gardens, rice fields, and homegardens. Rapid population expansion, illicit bird shooting, forest degradation and conversion, and pesticide pollution have reduced rural bird species diversity. This study examined bird diversity in natural forests, coffee agroforestry, vegetable gardens, and bird hunting. Quantitative and qualitative research were used. The point count approach investigates bird species and populations, whereas detailed interviews with knowledgeable informants are used to study bird hunting. In natural forests, vegetable gardens, and coffee agroforestry, 67 species from 39 bird groups were found. The bird species diversity index in three habitats: vegetable garden (H'=2.59), coffee agroforestry (H'=2.97), and natural forest (H'=2.96). Based on the Sorensen Similarity Index, bird species in in vegetable garden and coffee agroforestry, vegetable garden and natural forest, and coffee agroforestry and natural forest had a similarity index of 31.03%, 22.22%, and 52.05%, respectively. These findings suggest that bird species may prefer coffee agroforestry over vegetable gardens. The coffee agroforestry system can generate complex vegetation canopy stratification with a multi-layered vegetation canopy, resembling natural forest stratification. Illegal hunting of bird species for trade is one of the causes of the decline in bird populations in rural ecosystems of West Java, including in Cijambu Village. The coffee agroforestry provides a habitat for rural birds.